Elimination of Dog-Mediated Human Rabies Deaths by 2030: Needs Assessment and Alternatives for Progress Based on Dog Vaccination - Wallace, Ryan M.; Undurraga, Eduardo A.; Blanton, Jesse D.; Cleaton, Julie; Franka, Richard (Frontiers in Veterinary Science, 2017)
Background. Rabies imposes a substantial burden to about half of the world population. The World Health Organization (WHO), World Organization for Animal Health, and the Food and Agriculture Organization, have set the goal of eliminating dog-mediated human rabies deaths by 2030. This could be achieved largely by massive administration of post-exposure prophylaxis –in perpetuity–, through elimination of dog rabies, or combining both. Here we focused on the resources needed for the elimination of dog rabies virus by 2030. Materials and methods. Drawing from multiple datasets, including national dog vaccination campaigns, rabies literature, and expert opinion, we developed a model considering country-specific current dog vaccination capacity to estimate the years and resources required to achieve dog rabies elimination. Resources were determined based on four factors: a) country development status, b) dog vaccination costs, c) dog rabies vaccine availability, and d) existing animal health workers. Our calculations were based on the WHO’s estimate that vaccinating 70% of the dog population for seven consecutive years would eliminate rabies. Findings. If dog rabies vaccine production remains at 2015 levels, we estimate that there will be a cumulative shortage of 7.5 billion doses to meet expected demand to achieve dog rabies elimination. We estimated a present cost of $6,300 million (m) to eliminate dog rabies in all endemic countries, equivalent to a $3,900m gap compared to current spending. To eliminate dog rabies, the vaccination workforce may suffice if all public health veterinarians in endemic countries were to dedicate three months each year to dog rabies vaccination. We discuss implications of technology improvements, including population management, vaccine price reduction, and increases in dog-vaccinating capacities. Conclusion. Our results highlight the resources needed to achieve elimination of dog-mediated human rabies deaths by 2030. As exemplified by multiple successful disease elimination efforts, one size does not fit all. We suggest pragmatic and feasible options towards global dog rabies elimination by 2030, while identifying several benefits and drawbacks of specific approaches. We hope that these results help stimulate and inform a necessary discussion on global and regional strategic planning, resource mobilization, and continuous execution of rabies virus elimination.